Antibiofilm Efficiency of CaF2/TiO2 Strontium Borate Bioactive Glass Composites against Pseudomonas aeruginosa and Gamma Radiation Effect - Eman Mohamed Abou Hussein; Noha Mohamed Abou Hussien; Sabrin Ragab Mohamed Ibrahim; Mahmoud Abdelkhalek Elfaky; Tamer Dawod Abdelaziz (Universitas Gadjah Mada, 2024)
Microbial drug resistance has emerged as one of the most fundamental health threats. The current work aims to assess the antibacterial and antibiofilm potential of strontium borate bio-glasses (BBGs). Three CaF2/TiO2 strontium borate compositions have been prepared through melting annealing methods. The XRD pattern displays the amorphous nature of the glassy samples. The primary structural components of the borate, the trigonal BO3 and tetrahedral BO4 group, can be observed in FTIR spectra. Sharpness and shifting peaks to longer wavenumbers were evident after 40 kGy of gamma radiation. In contrast, density and molar volume (Vm) reveal an obvious change after irradiation. The agar diffusion technique was conducted as a preliminary screening of the antibacterial activity against Pseudomonas aeruginosa. The studied samples possessed no antimicrobial activity toward this strain; however, samples with 2% CaF2 strontium borate (T1) and 5% TiO2 strontium borate (T3) had higher biofilm inhibition potential (inhibition percentages of 75.17 and 65.77%, respectively). The gamma irradiation procedure had an unexpected detrimental effect on the bio-glass antibiofilm activity, making it unsuitable for use in sterilization procedures. Collectively, BBGs could be further investigated as possible antibacterial agents against biofilm-producing resistant strains.